Investment finance and financial sector development - Shubhomoy Ray (Asian Development Bank Institute (ADBI), 2015)
Investment in infrastructure for increasing trade and connectivity in South Asia and Southeast Asia has been impacted by a reduction in commercial bank participation in project financing, which has significantly increased the role of multilateral financial institutions and export credit agencies. The financing model needs to change to more sustainable local market and local currency financing by harnessing domestic savings, and this will be crucial if the region is to procure investments of an estimated 3.6 trillion by 2020 for financing of its infrastructure and connectivity projects. Increased connectivity between South and Southeast Asia can play an important role in improving efficiency and productivity by having more efficient industries based on comparative advantage, enlarging the overall market size, and increasing market access. However, such economic integration faces a multitude of challenges relating to cross-border infrastructure links, weak trade facilitation, shortages of infrastructure financing, non-tariff barriers, restrictions on foreign direct investment, and weak institutional coordination. Improvement in these issues would require large-scale public and private sector investment, supplemented by commercially viable credit. This study analyzes the means and constraints in funding cross-border connectivity projects. Using the most recent data from sources including the World Bank, ADB, and other financing and research institutions, barriers in financing cross-border projects are explored and analyzed with the help of case studies. This research brings to the fore the potential benefits of regional funding platforms and the role of multilaterals in resolving such barriers.
Keywords: G15; G21; G23; H44; H54; H87; 330; infrastructure; infrastructure financing; project finance; bond markets; public-private partnerships; public finance; multilateral banks